2001
DOI: 10.1023/a:1013694606500
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Water-immersion restraint stress increased secretory activity of mast cells and led to the formation of erosive lesions in the gastric mucosa. Intraperitoneal administration of amylin in a dose of 0.5 microg/kg 1 h before stress suppressed degranulation of mast cells and decreased the severity of gastric mucosa damages. In in vitro experiments amylin abolished the activating effects of acetylcholine and bradykinin on mast cell degranulation. Amylin-induced stabilization of activated mast cells probably underli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The mechanism underlying the protective effect of glyprolines on contractile activity of lymphatic vessels remains unclear. Our previous studies showed that the ability of glyprolines to decrease the severity of stressogenic microcirculatory disorders in rat mesentery is associated with the stabilizing effect on mast cells [5]. Mediators of these cells modulate vascular permeability and contribute to the development of edema during inflammation [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism underlying the protective effect of glyprolines on contractile activity of lymphatic vessels remains unclear. Our previous studies showed that the ability of glyprolines to decrease the severity of stressogenic microcirculatory disorders in rat mesentery is associated with the stabilizing effect on mast cells [5]. Mediators of these cells modulate vascular permeability and contribute to the development of edema during inflammation [9].…”
Section: Resultsmentioning
confidence: 99%
“…Response of rat mesenteric lymphatic vessels to application of NE 2 h after administration of physiological saline (1), thioglycollate (2), thioglycollate and PGP (3), thioglycollate and PG (4), thioglycollate and GP(5), and thioglycollate and glycine(6). p<0.001: *compared to group 1; + compared to group 2.…”
mentioning
confidence: 99%
“…The scientific framework presented in A is based on current evidence for (i) presence of CGRP in peptidergic C but not Aδ-fibres 36 , 42 ; (ii) presence of CGRP receptors in Aδ but not C-fibres 34 and in WDR and HT neurons 43 , 44 ; (iii) CGRP release from central branches of C-fibres in the medullary and upper cervical dorsal horn 29 , 45 ; (iv) a distinction between physiological and molecular processes that govern activation versus sensitization of central nociceptive neurons; (v) CGRP predominant role in neuronal sensitization 46 , 47 ; (vi) predominant contribution of C-fibre nociceptors to the development of central sensitization 48 ; (vii) presence of AMY 1 receptors in both Aδ and C-fibres 49 , 50 ; (viii) amylin analogue ability to provoke migraine-like headache 51 ; (ix) high level of amylin in the plasma of chronic migraine patients 52 ; and (x) speculation about pancreatic (b-cells) origin of amylin in the dura. 53 , 54 Based on the above, we are proposing that by neutralizing the CGRP peptide, anti-CGRP monoclonal antibodies can prevent activation of both the CLR-RAMP1(CGRP receptor) and CTR-RAMP1 (Amy1 receptor) by CGRP, but not the activation of the CTR-RAMP1 by amylin (illustrated in B ). In contrast, atogepant’s ability to block the CLR-RAMP1 as well as the CTR-RAMP1 55-57 can prevent their activation by CGRP as well as amylin (illustrated in C ).…”
Section: Discussionmentioning
confidence: 99%
“…Conceptual evidence for amylin's role in migraine includes reports of an amylin analogue's (pramlintide) ability to trigger a migraine-like headache in patients, 51 and its high plasma level in chronic migraine patients. 52 Given that the origin of amylin in the plasma is pancreatic β-cells, 53 and that their ability to self-regulate amylin secretion is commonly determined/affected by consumption of glucose, fats and proteins, 53 stress 54 and melatonin (a hormone primarily known for its role in regulating sleep-wake cycles) secretion, 76 it is tempting to hypothesize that amylin secretion may play a role in the mechanisms by which migraine is triggered by food, stress and sleep.…”
Section: Discussionmentioning
confidence: 99%